COVID-19 Effect on Tourism: Measuring Guest Behavior towards Hotel Industry Using Ordered Logistic Regression - Aryal, Rupesh; K.C., Anup; Paudel, Udaya Raj; Mahapatra, Sushanta Kumar; Khanal, Ghanashyam; Shrestha, Kolin Kiran; Kumari, Devi (Economic Journal of Development Issues, 2024)
The global COVID-19 pandemic significantly impacted the Nepalese hotel industry due to government-imposed lockdowns and travel restrictions. This led to decreased earnings, higher unemployment, and a noticeable shift in guest behavior. In this context, the study analyzes the impact of COVID-19 on guest behavior towards the hotel industry in the Kathmandu Valley. This study utilizes an explanatory research design and gathers data from 260 participants through structured questionnaires, administered with the assistance of the KOBO Toolbox within the Kathmandu Valley. Inferential analysis was conducted using an ordered logistic model. The findings indicate that the pandemic has indeed had an impact on guest behavior within the hotel industry. Additionally, factors such as gender, education level, profession, reference group, security, attitude, and beliefs play a significant role in shaping guest behavior toward the hotel industry. We also find that most individuals visit hotels for personal reasons, and guests generally have a moderate level of awareness regarding COVID-19. In conclusion, hotels should enhance their services and maintain a hygienic environment to address these issues. In this regard, this study will benefit researchers, the hotel industry, the travel and tourism sector, policymakers, marketing agencies, and more.